Incidental finding of lipaemia retinalis on diabetic retinal screening. (20th October 2021) - Kempegowda, Punith; Chen, Wentin; Melson, Eka; Leong, Annabelle; Amrelia, Prashant; Syed, Ateeq
Abstract : Summary: A 37-year-old female of South Asian origin was referred to our diabetes clinic for evaluation of an unusual finding during her retinal screening. Her retinal blood vessels appeared white in contrast to the normal pink-red colour. She had type I hyperlipidaemia, confirmed by genotype, and was recently diagnosed with diabetes, secondary to pancreatic insufficiency, for which she had suboptimal control and multiple hospitalisations with recurrent pancreatitis. On examination, she had multiple naevi on her skin; the rest of the examination was unremarkable. The patient did not report any visual disturbances and had intact visual acuity. Investigations showed raised total cholesterol (12.5 mmol/L) and triglycerides (57.7 mmol/L). Following evaluation, the patient was diagnosed with lipaemia retinalis, secondary to type I hyperlipidaemia. The patient was managed conservatively to reduce the cholesterol and triglyceride burdens. However, therapies with orlistat, statin, fibrates and cholestyramine failed. Only a prudent diet, omega-3 fish oil, medium-chain triglycerides oil and glycaemic control optimised with insulin showed some improvements in her lipid profile. Unfortunately, this led her to becoming fat-soluble vitamin deficient; hence, she was treated with appropriate supplementation. She was also recently started on treatment with volanesorsen. Following this, her lipid parameters improved and lipaemia retinalis resolved. Learning points: Lipaemia retinalis is an uncommon incidental finding of type I hyperlipidaemia that may not affect vision. Management of associated dyslipidaemia is challenging with minimal response to conventional treatment. Increased awareness of lipaemia retinalis and specialist management is needed as part of regular patient monitoring and personalised management.